Model MI-PSAIK: Model Integratif Pengajaran Sastera Arab Berdasarkan Pendekatan Ibnu Khaldun - Nurhasma Muhamad Saad; Ab Adly Rabbanie Ab Rahim; Margaret Anthoney; Yee Chin Yip (UKM Press, 2026)
Tier 3- Indexed by MyCite